PENGARUH TEKANAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT XXX - Wulan, Suci Yolanda; Susanto, Andi Heru (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2022)
Employee performance is important in a company, with increasing employee performance, it is expected to make it easier for the company to achieve its goals. This study aims to determine the effect of work pressure and motivation on employee performance. This study used an associative approach with a sample of 100 employees. The instrument used is a questionnaire. Instrument quality testing includes validity and reliability tests. Data analysis uses descriptive analysis, while for hypothesis testing it uses multiple linear analysis. The results showed that partially the working pressure had a positive and significant effect on performance with a calculated t value of 4,536 > 1,98397 t table with a significance value of 0,000 < 0,05. Motivation had a negative and significant effect on performance partially with a calculated t value –2,374 < 1,98397 t table with a significance value of 0,020 < 0,05. Work pressure and motivation had a positive and significant effect on simultaneous performance with a calculated f value of 12,540 > 3,09 f table with a significance value of 0,000 < 0,05 and an R- square value of 20,5%. This analysis was only carried out on PT XXX only and does not take into account other variables.